Sistem Proteksi Pelepasan Beban dengan Metode Descending Menggunakan Macro VBA - Muhammad Fajar; Herfia Rhomadhona; Khairul Anwar Hafizd (Teknik Informatika, Politeknik Negeri Tanah Laut, 2019)
The last few months, PT. PLN WKSKT deliberately goes out to prevent the failure of the generator system network. Blackouts occur because there are uneven load uses. The use of the largest load is in the Barikin transmission line scheme towards the Tanjung and Cempaka direction. Both schemes are crucial load conditions when there is a disruption in the transmission line. This can interfere with the transmission of the load on targets that are in the two schemes, cause trips and blackouts. To resolve the issue, PT. PLN WKSKT create a special scheme for the protection system loads on specific targets. Which system can sort the target load from large to small. Descending is a sorting method that can complete the purpose of a protection system. With this method the target load is sorted and then calculated in VBA macros. The target load that has been sorted is then added to the equivalent of the line transfer. Calculations performed on VBA macros aim to obtain load release status based on enable, ready and trip indications. All three indicators used to monitor the load condition real time. So that the protection system is able to avoid interference that can cause black out on the electrical system.